ANALISIS PERKEMBANGAN DAN PENGEMBANGAN ROTI BAKAR SANTRI (RBS) CURAH JERU TENGAH - Rafiyan Nurus Solihin; Febri Ariyantiningsih; Mohammad Ubaydillah; Moh Heri Irwansyah; Bintang Arya Wirahman (Fakultas Ekonomi dan Bisnis, 2025)
Roti Bakar Santri (RBS) is a micro-enterprise operating in the culinary sector and is located in Curah Jeru Tengah Village. This study aims to determine the development of the Roti Bakar Santri business and the factors influencing its sustainability and development. The research method used is a qualitative method with a descriptive approach, through data collection techniques such as observation, interviews, and documentation. The results show that Roti Bakar Santri has experienced quite significant growth since its establishment in 2007, marked by an increase in production volume, the addition of sales carts, and the expansion of offline and online marketing. A structured production strategy, quality raw materials, innovative flavor variants, and affordable prices are the main supporting factors in the development of this business. The inhibiting factors faced include obstacles in online order distribution and the risk of product unsold. However, these obstacles can be overcome through a flexible sales system and good business management. Thus, Roti Bakar Santri can be said to be a local business with great potential to continue to grow and contribute to the economy of the surrounding community.